Analysis Of Early Marriage And Other Factors On Stunting Incidence In The Work Area Of Prabugantungan Puskesmas Lebak District - Susilawati Susilawati; Nanik Yuliwati (International Journal Of Health Science, 2023)
Background Stunting is a chronic nutritional problem caused by a long-term lack of nutrients. Early marriages that are commonly practiced in the community can have a negative effect on the health conditions of mothers and children and can increase the incidence of stunting. Objective to see if there is a relationship between early marriage and other factors on the incidence of stunting in the working area of the Prabugantungan Health Center, Lebak Regency Research methods This type of research is quantitative research with a Cross Sectional Study approach. Using a cluster sampling technique with a total sample of 128 with the criteria of a village with a high stunting rate. Statistical analysis test with Chi-Square with a significance level of α = 5%. Research result Most of the toddlers have normal nutritional status, namely 89.1% and only 10.9% of them are stunted. 78.1% of mothers were married at the age of 19 and over and a small number of mothers (21.9%) had early marriages. There is a relationship between early marriage and the incidence of stunting in the Work Area of the Prabugantungan Health Center (p-Value 0.007). There is no relationship between education, work, and place of delivery of mothers with the occurrence of stunting in Work Area of the Prabugantungan Health Center. Conclusions and recommendations Midwives need to socialize the prevention of early marriage in adolescents in anticipation of stunting prevention by involving cross-sectors.